The effect of an e-learning training program on the performance of some technical and tactical skills among handball players aged 17 to 19 - Sedira, saad (sports creativity, 2025)
The current century is witnessing significant advancements in sports training and athletic achievements, thanks to the efforts of researchers who are leveraging other sciences (biomechanics, psychology, statistics, sports medicine, etc.) in sports training to develop and enhance performance levels and reach their full potential. Consequently, training science has evolved rapidly, and its theories have taken a new direction to keep pace with modern trends across all disciplines. This involves planning training programs based on scientific principles that focus on skill and technical performance, as well as tactical movements, in light of the increasing professionalism and the complexities it entails. Sports training aims not only to improve and develop various physical abilities but also to acquire athletic skills through continuous learning and consistent training. However, achieving this is no easy feat today. Reaching a high level in sports in general, and handball in particular, will not achieve the desired goals unless it relies on sports planning based on scientific principles in the field of training. This is what Wei Neck emphasized, as he believes that the ability to win and achieve results depends on attaining the highest possible level of physical, technical, tactical, and psychological capabilities. Therefore, there must be a systematic and organized plan based on scientific principles in the field of modern sports training. Many previous studies and research have demonstrated the necessity of focusing on this group by developing modern scientific programs and relying on qualified professionals in this field. The development that modern handball has witnessed is primarily due to attention to several aspects, foremost among them the coach, the player, and the training programs. The coach is responsible for training the players through standardized programs based on scientific principles in order to reach the highest levels of performance and achieve good results. Anyone observing the current state and level of Algerian handball, particularly the training programs implemented for youth categories regarding skills and tactics, will immediately notice the lack of variety and utilization of offensive and defensive skills. The constant, unsystematic changes in defensive and offensive tactics and game plans, depending on the playing style, have negatively impacted the quality of training provided to this age group. For an attacking team to score a goal, it must utilize the players' individual skills, including shooting, passing, dribbling, numerical superiority, crossing, and positional changes to create gaps in the defense. The effectiveness of the offensive and defensive formations depends on the ability of the tactical work to make the most of the offensive movements within the formations of play, to free the shooter or finisher away from the defensive field to shoot freely to confirm scoring the goal. The finisher may be free to shoot with the goalkeeper's save or the ball hitting the post or crossbar. Here the achievement has been achieved but at a lower level. The evaluation of the offensive work here depends on the level of achievement, which is one of the indicators describing the level of mastery of the technical and tactical performance. As for the defensive aspect, the players must use different defensive skills in an attempt to close gaps or cover an empty space or advance forward to obstruct shooting or passing and try to stop the progress of the attack.